Bioclimatic regions influence genetic structure of four Jordanian Stipa species. (17th December 2012) - Hamasha, H. R.; Schmidt‐Lebuhn, A. N.; Durka, W.; Schleuning, M.; Hensen, I.; Byers, D.
Abstract Strong environmental gradients can affect the genetic structure of plant populations, but little is known as to whether closely related species respond similarly or idiosyncratically to ecogeographic variation. We analysed the extent to which gradients in temperature and rainfall shape the genetic structure of four Stipa species in four bioclimatic regions in Jordan. Genetic diversity, differentiation and structure of Stipa species were investigated using amplified fragment length polymorphism (AFLP) molecular markers. For each of the four study species, we sampled 120 individuals from ten populations situated in distinct bioclimatic regions and assessed the degree of genetic diversity and genetic differentiation within and among populations. The widespread ruderals Stipa capensis and S. parviflora had higher genetic diversity than the geographically restricted semi‐desert species S. arabica and S. lagascae. In three of the four species, genetic diversity strongly decreased with precipitation, while genetic diversity increased with temperature in S. capensis. Most genetic diversity resided among populations in the semi‐desert species (ΦST = 0.572/0.595 in S. arabica/lagascae) but within populations in the ruderal species (ΦST = 0.355/0.387 S. capensis/parviflora). Principal coordinate analysis (PCoA) and STRUCTURE analysis showed that Stipa populations of all species clustered ecogeographically. A genome scan revealed that divergent selection at particular AFLP loci contributed to genetic differentiation. Irrespective of their different life histories, Stipa species responded similarly to the bioclimatic gradient in Jordan. We conclude that, in addition to predominant random processes, steep climatic gradients might shape the genetic structure of plant populations.